(untitled) (Fiep Bulletin - online, 2015)
The objective of the present study was to analyze the adult apprentices’ of muscular activity of both sexes corporal composition, with age group between 30 and 50 years. The study carcateriza-if I eat a traverse experimental research with quantitative approach. The group convenience amostral was composed by 30 muscular activity apprentices, being 15 women and 15 men, all volunteers (the), in the age group among 30 to 50 years of age; customers of Clube S.E.R.A’S academy (Sporting Society and Recreational Altoniense) of the municipal district of Altônia - PR. For the collection of data the following protocols were used: In the statistical analysis of the work the "Test was used "t" of Students" for given pareados, having been adopted a level of significância of p <0,05. it was Used for statistical analysis the program Excel, Windows version 2003. With base in the obtained results, the conclusion was arrived that the practicing women of muscular activity after 4 months (powders test) of the first corporal evaluation (pré tests), they reduced the following components of the corporal composition: Corporal density, The results obtained in this study, pré-test and powder-test allowed to end that you/they exist women’s classification with overweight and obesity, and besides the with he/she practices her/it of muscular activity, it reduced the percentile of corporal fat and and increase of mass thin apprentices both muscular activity sexes. Percentile fat, absolute Fat and exempt mass of fat, as well as IMC (index of corporal mass). Already the group masculine amostral only presented decrease of the percentile of fat and increase of the muscular mass. It is ended that the practicing men of muscular activity presented smaller decrease of the percentile of corporal fat in relationship the women. In both practicing sexes of muscular activity there were a decrease of the percentile of fat and increase of thin mass; optimization of the muscular force; increase in the exempt mass of fat; increase of the muscular mass and an improvement of the life quality. However in the male group they presented a smaller decrease of the corporal composition, compared the pré-test and powder-test of the same group with the female group. In what he/she refers rest FC and effort, according to the results of the pré-test and powder-test of both groups, they obtained a decrease and alteration in the monitored heart frequency.